Optimal restructuring of distorted distribution system by teaching-learning-based optimisation. Issue 2 (3rd April 2019) - Sureshkumar, K.; Thiruvenkadam, S.
ABSTRACT: Distribution systems are basic connections between utility and utility clients. Distribution system restructuring is a standout among the most critical procedures took after for the control of energy loss. Because of the more utilisation of non-linear loads by the utility clients, more harmonics are being infused into distribution systems, which may prompt high distortion levels. To lessen the distortion level, power quality constraints are incorporated as one among the other working requirements with the primary goal. The essential goal is to limit the power loss cost of the distribution system while fulfilling the power flow, operational and power quality limitations. This paper proposes Teaching-Learning-Based Optimisation (TLBO) to take care of the issue. The backward-forward sweep Harmonic Load Flow (HLF) is utilised to assess the harmonics present in the distribution system, which has been coordinated with Teaching Learning Algorithm (TLA). The proposed hybrid TLA-HLF strategy has been validated with IEEE-33 bus distribution and 83-bus Taiwan Power Distribution Company system.